Fatiguing upper body aerobic exercise impairs balance - Douris, P. C.; Handrakis, J. P.; Gendy, J.; Salama, M.; Kwon, D.; Brooks, R.; Salama, N.; Southard, V. (The Journal of Strength and Conditioning Research, 2011)
There are many studies that have examined the effects of selectively fatiguing lower extremity muscle groups with various protocols, and they have all shown to impair balance. There is limited research regarding the effect of fatiguing upper extremity exercise on balance. Muscle fiber-type recruitment patterns may be responsible for the difference between balance impairments because of fatiguing aerobic and anaerobic exercise. The purpose of our study was to investigate the effect that aerobic vs. anaerobic fatigue, upper vs. lower body fatigue will have on balance, and if so, which combination will affect balance to a greater degree. Fourteen healthy subjects, 7 men and 7 women (mean age 23.5 ± 1.7 years) took part in this study. Their mean body mass index was 23.6 ± 3.2. The study used a repeated-measures design. The effect on balance was documented after the 4 fatiguing conditions: aerobic lower body (ALB), aerobic upper body (AUB), anaerobic lower body, anaerobic upper body (WUB). The aerobic conditions used an incremental protocol performed to fatigue, and the anaerobic used the Wingate protocol. Balance was measured as a single-leg stance stability score using the Biodex Balance System. A stability score for each subject was recorded immediately after each of the 4 conditions. A repeated-measures analysis of variance with the pretest score as a covariate was used to analyze the effects of the 4 fatiguing conditions on balance. There were significant differences between the 4 conditions (p = 0.001). Post hoc analysis revealed that there were significant differences between the AUB, mean score 4.98 ± 1.83, and the WUB, mean score 4.09 ± 1.42 (p = 0.014) and between AUB and ALB mean scores 4.33 ± 1.40 (p = 0.029). Normative data for single-leg stability testing for this age group are 3.9 ± 1.9. Higher scores reflect greater balance deficits. The AUB condition produced the greatest balance deficit. Our data provide evidence of the important role of the upper body in maintaining unilateral standing balance and supports its inclusion as part of rehabilitation and training protocols designed to improve balance.